Citrobacter rodentium subverts ATP flux 1 and cholesterol homeostasis in 2 intestinal epithelial cell in vivo - Berger,C; Crepin,V; Roumeliotis,TI; Wright,JC; Carson,D; Pevsner-Fischer,M; Furniss,RCD; Dougan,G; Bachash,M; Yu,L; Clements,A; Collins,JW; et al. (Cell Metabolism, 2017)
The intestinal epithelial cells (IECs) that line the gut form a robust line of defense against ingested pathogens. We investigated the impact of infection with the enteric pathogen Citrobacter rodentium on mouse IEC metabolism using global proteomic and targeted metabolomics and lipidomics. The major signatures of the infection were upregulation of the sugar transporter Sglt4, aerobic glycolysis, and production of phosphocreatine, which mobilizes cytosolic energy. In contrast, biogenesis of mitochondrial cardiolipins, essential for ATP production, was inhibited, which coincided with increased levels of mucosal O2 and a reduction in colon-associated anaerobic commensals. In addition, IECs responded to infection by activating Srebp2 and the cholesterol biosynthetic pathway. Unexpectedly, infected IECs also upregulated the cholesterol efflux proteins AbcA1, AbcG8, and ApoA1, resulting in higher levels of fecal cholesterol and a bloom of Proteobacteria. These results suggest that C. rodentium manipulates host metabolism to evade innate immune responses and establish a favorable gut ecosystem.